Child Friendly Villages as an Effort to Prevent a Child as Victims and as Perpetrator Crimes - Erdianti, Ratri Novita; Wasis, Wasis; Al-Fatih, Sholahuddin (Universitas Negeri Semarang, 2022)
The state has a crucial responsibility to ensure legal protection for children, as they are the future pillars of our society. Establishing policies for child-friendly cities is paramount in safeguarding their rights. According to Minister of Women's and Children’s Empowerment Regulation Number 11 of 2011, a Child Friendly City integrates governmental, communal, and corporate resources to develop a system focused on children's rights. This entails comprehensive and sustainable policies, programs, and activities to ensure the fulfillment of children's rights across various domains, such as civil liberties, family welfare, health, education, recreation, cultural engagement, and special protection. The implementation of a Child Friendly City primarily aims at upholding children's rights, including protecting them from vulnerability to criminal activities as either perpetrators or victims. Dadaprejo Village, Indonesia, facing issues of escalating youth delinquency, is in dire need of intervention to address these challenges. Collaborative efforts encompassing legal and psychological counseling, consultation, and support are crucial to mitigate the problems plaguing Dadaprejo Village. By providing assistance tailored to the village's specific needs, the aim is to prevent children from falling prey to criminal behaviors, such as substance abuse, and to steer them away from engaging in criminal acts. Ultimately, the objective is to transform Dadaprejo Village into a child-friendly community that prioritizes the well-being and safety of its children, thus fostering a healthier environment free from criminal influences.